Perlindungan Hukum Bagi Anak yang Melakukan Tindak Pidana Penyalahgunaan Narkotika - Putu Krisna Widya Sujana; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2022)
BNN issued news that there was an increase in narcotics abuse among the younger generation, which is very dangerous for the nation's successors where there is no legal protection for perpetrators and victims of narcotics abuse who are still minors. This thesis discusses the legal protection given to minors who are entangled in narcotics crimes. Based on the description above, the formulation of the problem is as follows 1) What is the legal protection for children who are entangled in criminal cases of narcotics abuse? 2) What are the criminal sanctions for children who abuse narcotics? This research uses a research type. Based on the research, it was found that legal protection aimed at protecting children was given by the government to children affected by narcotics cases both as owners and users of narcotics, but the government provided protection for minors through Child Protection. it does not include what is often found from this protection, when a child is in a narcotics crime case, the law cannot fully protect it because there is a norm vacuum in the Narcotics Law which is not clearly stated how the protection is aimed at children affected by narcotics crimes.